Estrategias tecnológicas innovadoras para incrementar el rendimiento durante la elaboración de quesos blandos - Audero, Gabriela Maria (2022)
Cheese yield and manufacturing efficiency are the main determinants of cheese production. profitability of cheese manufacturing plants. The most important factor affecting the cheese yield is the composition of the milk, in particular the concentrations of fats and proteins. An alternative used to standardize and increase the content of proteins in the milk to be processed, increasing cheese yield, consists of mixing milk with ultrafiltered milk concentrate (ULF) in the brew vat, in an amount to obtain the desired final concentration. The increase in protein content in the production milk, in addition to the impact on the cheese yield, allows obtaining a product with a differential nutritional value, due to the protein increase that it will have in its chemical composition. In the case of Argentine cheeses, this technology has been tested for soft cheeses, with little scientific information on the effect generated in the quality of the cheeses produced.